Bridge function for liquid Na - Baumketner, A.; Chushak, Ya. (Condensed Matter Physics, 1999)
Bridge function B(r) for liquid Na is calculated in the referense hypernetted chain approximation from the pair distribution function obtained by
means of MD simulations. A comparison with the bridge function obtained
in a Mori-Hoshino-Watabe scheme is made. The inﬂuence of the cut-off
radius and the MD sample size on the structure factor is investigated. Елементарні діаграми B(r) для рідкого Na розраховані в базисному
гіперланцюговому наближенні з парних функцій розподілу отриманих
методом МД. Проведено порівняння з B(r) в наближенні Морі-Хошіно-Ватабе. Досліджено залежність статичного структурного фактора
від радіуса обрізання базисної парної функції розподілу.